The Effect of Cashless Transactions on Customer Visits at Lotte Wholesale Balikpapan Retail Company: Pengaruh Transaksi Cashless Pada Kunjungan Customer Perusahaan Retail Lotte Grosir Balikpapan - Suhada; Ajeng Andriani Hapsari; Sitti Syamsiar Binti Muharram (Institute of Educational, Research, and Community Service, 2023)
This study aims to determine the effect of cashless transactions on customer visits of Lotte Wholesale Balikpapan Retail Company. A total of 4 transaction methods will be analysed, namely the use of QR Payment, ATM Card, DP transfer, Voucher. In the current digital era that is increasingly sophisticated, people are starting to apply and utilise digital payments when conducting financial transactions so that the use of cashless transactions is minimised. The purpose of this study is to analyse whether there is a significant change in cashless transactions from 2019 to 2022. The research method used in this research uses quantitative methods, with secondary data taken in the form of time series from 2019 - 2022. The results of this study show that Lotte Grosir Balikpapan has implemented several cashless payment systems that are currently more often used by modern society, with the highest achievement in the use of cashless payment methods occurring in 2020, which is the beginning of the COVID-19 pandemic